Antimicrobial Resistance Pilot Surveillance of Pigs and Chickens in Vietnam, 2017–2019 - Tuat, C. V.; Hue, P. T.; Loan, N. T. P.; Thuy, N. T.; Hue, L. T.; Giang, V. N.; Erickson, Vera I.; Padungtod, Pawin (Frontiers in Veterinary Science, 2021)
Antimicrobial use (AMU) and antimicrobial resistance (AMR) are a growing public health and economic threat in Vietnam. We conducted a pilot surveillance programme in five provinces of Vietnam, two in the South and three in the North, to identify antimicrobial resistance (AMR) in rectal swab samples from pigs and fecal samples from chickens at slaughter points during three different points in time from 2017 to 2019. Escherichia coli (E. coli) and non-typhoidal Salmonella (NTS) isolates were tested for antimicrobial susceptibility using disk diffusion assay for 19 antimicrobial agents belonging to nine antimicrobial classes and Etest for colistin (polymyxin). Almost all E. coli (99%; 1029/1042) and NTS (96%; 208/ 216) isolates were resistant to at least one antimicrobial agent; 94% (981/1042) of E. coli and 89% (193/216) of NTS isolates were multidrug-resistant (MDR). Higher proportions of E. coli and NTS isolated from chickens were resistant to all antimicrobial classes than those isolates from pigs. There was a significantly higher proportion of MDR NTS isolates from the southern provinces of Ho Chi Minh City and Long An (p = 0.008). Although there were increasing trends of NTS in proportion of resistance to fluoroquinolone over the three surveillance rounds, there was a significant decreasing trend of NTS in proportion of resistance to polymyxin (p = 0.002). It is important to establish an annual AMR surveillance program for livestock in Vietnam to assess the impact of interventions, observe trends and drive decision making that ultimately contributes to reducing AMR public health threat.